2022
DOI: 10.1108/ecam-10-2021-0953
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the trends and cost impact of COVID-19 OSHA citations on US construction contractors using machine learning and simulation

Abstract: PurposeOccupational Safety and Health Administration (OSHA) of the U.S. government ensures that all health and safety regulations, protecting the workers, are enforced. OSHA officers conduct inspections and assess fines for non-compliance and regulatory violations. Literature discussion on the economic impact of OSHA inspections with COVID-19 related citations for the construction sector is lacking. This study aims to investigate the relationships between the number of COVID-19 cases, construction employment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Other varied studies have been conducted in areas including health and safety management (Kum et al. , 2023; Sadeh et al. , 2023), construction performance (Gumusburun Ayalp and Civici, 2023), and construction supply chain management (Sutterby et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other varied studies have been conducted in areas including health and safety management (Kum et al. , 2023; Sadeh et al. , 2023), construction performance (Gumusburun Ayalp and Civici, 2023), and construction supply chain management (Sutterby et al.…”
Section: Introductionmentioning
confidence: 99%
“…Academia, in partnership with the industry, has reported on the impact of COVID-19 on the construction industry from various perspectives, such as the general construction industry (Ogunnusi et al, 2020), the health and safety of the construction workforce (Pamidimukkala et al, 2021), and the use and adoption of digital technologies . Other varied studies have been conducted in areas including health and safety management (Kum et al, 2023;Sadeh et al, 2023), construction performance (Gumusburun Ayalp and Civici, 2023), and construction supply chain management (Sutterby et al, 2023). Considering the challenges, how the pandemic and the associated mitigation measures have affected QA is still unclear.…”
mentioning
confidence: 99%
“…Jin et al (2022) estimated the impact of COVID-19 on international construction multi-projects by integrating a parametric model and Monte Carlo simulation. Sadeh et al (2022) found a positive relationship between the number of COVID-19 cases and the cost impact of COVID-19 Occupational Safety and Health Administration (OSHA) citations using machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Since the planning stage of a construction project was the most severely affected by the pandemic (Larasati et al, 2021), it is particularly essential to accurately diagnose and quantify the pandemic impacts on the demand movements in the construction market, which should be investigated ahead of a project planning for the success of both projects and businesses (Heron, 2021). A few quantitative studies only investigated the impact of COVID-19 on the overall construction industry through a one-time regional survey and interviews without considering the historical trends and seasonal cycles of the industry (Ling et al, 2022;Al Amri and Marey-Perez, 2020;Sadeh et al, 2022;Jin et al, 2022). Additionally, a detailed examination of more vulnerable building services and sectors in the construction industry to the pandemic is still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation